Negative thermal expansion material, manufacturing method thereof and composite material
Through the proportion of solid -soluble AL atoms in the composite oxide of copper tadpoles and adjusting the proportion of composition, the problems of insufficient negative thermal expansion performance in existing technologies and high industrialized manufacturing costs are solved, and the efficient negative thermal expansion performance of the material is improved and water resistance is improved.
Patent Information
- Application Number
- CN202380029457.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-06
- Filing Date
- 2023-02-24
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, there is room for improvement in the negative thermal expansion performance of copper-vana composite oxide, and its industrial manufacturing cost is high and its water resistance is insufficient, making it difficult to meet the needs of industrial applications.
By solid-dissolving Al atoms in the copper-vanadium composite oxide, a copper-vanadium composite oxide powder with the general formula CuxMyVzOt is formed, where M is a metal element other than Cu, V and Al, and its composition ratio is adjusted to improve the negative thermal expansion performance, and Reduce costs and improve water resistance by optimizing manufacturing processes.
The negative thermal expansion performance of the copper pupa composite oxides has been significantly improved, the thermal expansion coefficient is reduced, it is suitable for industrialized manufacturing and application, and the water resistance of the material is improved.
Smart Images

Figure CN119343319A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a negative thermal expansion material which shrinks when the temperature rises, a preparation method thereof and a composite material containing the negative thermal expansion material. Background Art
[0002] Most materials will increase in length, volume, etc. due to thermal expansion when the temperature rises. In contrast, there are also known materials that show negative thermal expansion (hereinafter also referred to as "negative thermal expansion materials"), in which the volume decreases when the temperature rises.
[0003] It is known that materials showing negative thermal expansion can be used together with other materials to suppress changes in the thermal expansion of the materials caused by changes in temperature.
[0004] As materials showing negative thermal expansion, for example, β-eucryptite, zirconium tungstate (ZrW2O8), zirconium phosphotungstate (Zr2WO4(PO4)2), Zn x Cd 1-x (CN)2, manganese nitride, bismuth-nickel-iron (complex) oxide, etc.
[0005] It is known that the linear expansion coefficient of zirconium phosphotungstate is -3.4 to -3.0 ppm / °C in the temperature range of 0 to 400°C, and the negative thermal expansion is relatively large. By using zirconium phosphotungstate together with a material showing positive thermal expansion (hereinafter sometimes referred to as "positive thermal expansion material"), a low thermal expansion material can be manufactured (see Patent Documents 1, 2, etc.). In addition, there is also a proposal to use a polymer compound such as a resin as a positive thermal expansion material together with a negative thermal expansion material (see Patent Document 3, etc.).
[0006] In addition, the following non-patent document 1 discloses that the copper-vanadium composite oxide of α-Cu2V2O7 has a linear expansion coefficient of -5 to -6 ppm / °C in the temperature range from room temperature to 200°C. In addition, a method for further improving the negative thermal expansion performance by replacing part of the Cu of the copper-vanadium composite oxide with at least one element selected from Zn, Ga, and Fe, or replacing part of the V with P has been proposed (Patent Documents 4 and 5).
[0007] In addition, the following patent document 6 also discloses a general formula Cu 2-x R x V 2-y M y A negative thermal expansion material represented by O7, wherein R is at least one element selected from Zn, Ga, Fe, Sn, and Mn, M is at least one element selected from Mg, Si, Al, Ti, Cr, Mn, Fe, Co, Ni, and Sn, and 0≤x<2, 0<y<2.
[0008] However, in Patent Document 6, the only products actually implemented as negative thermal expansion materials containing M element are products in which M element is Si and Mn. Therefore, there is no technical basis for the example of Al as M element in Patent Document 6.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2005-35840
[0012] Patent Document 2: Japanese Patent Application Publication No. 2015-10006
[0013] Patent Document 3: Japanese Patent Application Publication No. 2018-2577
[0014] Patent Document 4: Japanese Patent Application Publication No. 2019-210198
[0015] Patent Document 5: Chinese Patent Publication No. CN112390642
[0016] Patent Document 6: International Publication No. 2020 / 095518
[0017] Non-patent literature
[0018] Non-patent document 1: Ceramics International, Vo1.42, p17004-17008 (2016) Summary of the invention
[0019] Problems to be solved by the invention
[0020] However, the copper-vanadium composite oxide of Non-Patent Document 1 has the possibility of having a lower linear expansion coefficient than zirconium phosphotungstate, can be produced with a cheaper raw material system, is conducive to industrial production, and has excellent water resistance. In addition, there is a demand for further improving the negative thermal expansion performance.
[0021] Therefore, an object of the present invention is to provide a negative thermal expansion material having excellent negative thermal expansion performance. In addition, an object of the present invention is to provide the negative thermal expansion material in a method that is conducive to industrial production.
[0022] Technical solutions to solve problems
[0023] The above-mentioned problems are solved by the following present invention.
[0024] That is, the present invention (1) provides a negative thermal expansion material, characterized in that:
[0025] The copper-vanadium composite oxide powder comprising Al atoms solid-dissolved therein is represented by the following general formula (1), Cux M y V z O t (1)
[0026] In the formula, M represents a metal element with an atomic number of 11 or higher other than Cu, V and Al, x represents 1.60≤x≤2.40, y represents 0.00≤y≤0.40, z represents 1.70≤z≤2.30, and t represents 6.00≤t≤9.00. Among them, 1.00≤x+y≤3.00. Moreover, when the M element is contained, the atomic conversion mole number of Al atoms> the atomic conversion mole number of M atoms.
[0027] Effects of the Invention
[0028] According to the present invention, a negative thermal expansion material having excellent negative thermal expansion performance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the X-ray diffraction pattern of the negative thermal expansion material sample obtained in Example 1.
[0030] Figure 2 This is the X-ray diffraction pattern of the negative thermal expansion material sample obtained in Example 2.
[0031] Figure 3 This is the X-ray diffraction pattern of the negative thermal expansion material sample obtained in Example 3.
[0032] Figure 4 This is the X-ray diffraction pattern of the negative thermal expansion material sample obtained in Comparative Example 1.
[0033] Figure 5 This is a SEM photograph of the negative thermal expansion material sample obtained in Example 4 (magnification 400). DETAILED DESCRIPTION
[0034] Hereinafter, the present invention will be described based on preferred embodiments.
[0035] The negative thermal expansion material of the present invention is characterized by comprising a copper-vanadium composite oxide powder represented by the following general formula (1) in which Al atoms are solid-dissolved.
[0036] Cu x M y V z O t (1)
[0037] In the formula, M represents a metal element with an atomic number of 11 or higher other than Cu, V and Al, x represents 1.60≤x≤2.40, y represents 0.00≤y≤0.40, z represents 1.70≤z≤2.30, and t represents 6.00≤t≤9.00. Among them, 1.00≤x+y≤3.00. Moreover, when the M element is contained, the atomic conversion mole number of Al atoms> the atomic conversion mole number of M atoms.
[0038] The copper-vanadium composite oxide containing Al atoms in a solid solution is a copper-vanadium composite oxide represented by the following general formula (1).
[0039] Cu x M y V z O t (1)
[0040] In the general formula (1), M is a metal element contained as required for the purpose of improving negative thermal expansion performance, adjusting negative thermal performance, improving resin dispersibility, etc. M represents a metal element with an atomic number of 11 or more other than Cu, V and Al, and is preferably one or more selected from Zn, Ga, Fe, Mg, Co, Mn, Ba and Ca, and particularly Ca, which can form a product having excellent negative thermal expansion performance, and from this perspective, is preferred.
[0041] In the general formula (1), x represents 1.60≤x≤2.40, and preferably 1.70≤x≤2.30. When x is within the above range, the negative thermal expansion performance can be further increased.
[0042] In the general formula (1), y represents 0.00≤y≤0.40, preferably 0.00≤y≤0.35. When y is within the above range, the negative thermal expansion performance can be further increased.
[0043] In the general formula (1), z represents 1.70≤z≤2.30, and preferably 1.80≤z≤2.20. When z is within the above range, the negative thermal expansion performance can be further increased.
[0044] In the general formula (1), t represents 6.00≤t≤9.00, preferably 6.00≤t≤8.00. When t is within the above range, the negative thermal expansion performance can be further increased.
[0045] In the general formula (1), x+y is 1.00≤x+y≤3.00, preferably 1.50≤x+y≤2.50. When x+y is within the above range, the negative thermal expansion performance can be further increased.
[0046] In the general formula (1), when the M element is contained, the atomic-equivalent molar number of Al atoms>the atomic-equivalent molar number of M atoms.
[0047] In the negative thermal expansion material of the present invention, Al atoms are solid-dissolved in the copper-vanadium composite oxide represented by the general formula (1). That is, the negative thermal expansion material of the present invention comprises the copper-vanadium composite oxide represented by the general formula (1), and in the copper-vanadium composite oxide, Al atoms are solid-dissolved and contained inside the particles. In a conventional composite of a negative thermal expansion material and Al metal, Al metal exists only in a manner of firmly adhering to the particles of the negative thermal expansion material, rather than Al atoms being solid-dissolved inside the particles of the negative thermal expansion material as shown in the present invention.
[0048] Since the negative thermal expansion material of the present invention is a copper-vanadium composite oxide powder represented by the general formula (1) in which Al atoms are solid-dissolved, the negative thermal expansion performance is improved compared with the copper-vanadium composite oxide powder having the same composition as the general formula (1) in which Al atoms are not solid-dissolved. That is, since the negative thermal expansion material of the present invention is a copper-vanadium composite oxide powder represented by the general formula (1) in which Al atoms are solid-dissolved, the thermal expansion coefficient is reduced compared with the copper-vanadium composite oxide powder having the same composition as the general formula (1) in which Al atoms are not solid-dissolved.
[0049] In the negative thermal expansion material of the present invention, the content of Al atoms is preferably 100 to 30,000 mass ppm, more preferably 500 to 28,000 mass ppm, and particularly preferably 1,000 to 26,000 mass ppm. Since the content of Al atoms in the negative thermal expansion material is within the above range, it is preferred that the negative thermal expansion material exhibits excellent negative thermal expansion performance in a single phase in X-ray diffraction. It should be noted that in the present invention, the content of Al atoms in the negative thermal expansion material can be obtained by analyzing the solution of the negative thermal expansion material after acid decomposition by ICP luminescence method.
[0050] The BET specific surface area of the negative thermal expansion material of the present invention is preferably, but not particularly limited to, 0.05 to 50 m 2 / g, particularly preferably 0.1 to 10 m 2 / g, more preferably 0.1 to 5 m 2 When the BET specific surface area of the negative thermal expansion material is within the above range, the negative thermal expansion material can be easily handled when used as a filler for resin, glass, or the like.
[0051] The average particle size of the negative thermal expansion material of the present invention is preferably, but not particularly limited to, an average particle size of 0.1 to 100 μm, particularly preferably 0.3 to 80 μm, as determined by scanning electron microscopy. By making the average particle size of the negative thermal expansion material within the above range, it is possible to facilitate the operation when the negative thermal expansion material is used as a filler for resins, glass, etc. It should be noted that in the present invention, the average particle size of the negative thermal expansion material is the arithmetic mean of the particle sizes of 50 particles randomly selected at a magnification of 1000 times in scanning electron microscopy observation as the average particle size. At this time, the particle size of each particle refers to the maximum length (maximum length) of the line segment that crosses the two-dimensional projection image of the particle.
[0052] The particle shape of the negative thermal expansion material of the present invention can be, but is not particularly limited to, for example, spherical, granular, plate-like, flaky, whisker-like, rod-like, filamentous, or fragmentary. However, from the perspective of being able to suppress the generation of particulate components caused by debris during mixing with the positive thermal expansion material and achieve more uniform mixing, the particle shape is more preferably a shape containing a large number of spherical particles.
[0053] It should be noted that in the present invention, the particle shape is spherical but not necessarily a perfect sphere. In the present invention, spherical refers to a shape having a sphericity of 0.70 or more and 1.00 or less.
[0054] In the present invention, the sphericity is determined by the following formula (1) based on the parameters obtained by electron microscope observation of a sample at a magnification of 100 to 1000 and image analysis.
[0055] Sphericity = area equivalent circle diameter / circumscribed circle diameter (1)
[0056] In formula (1), the area equivalent circle diameter refers to the diameter of a circle whose circumference is equal to the circumference of a particle. The circumscribed circle diameter refers to the longest particle diameter of a particle.
[0057] In the negative thermal expansion material of the present invention, the content ratio of spherical particles with a sphericity of 0.70 or more and 1.00 or less is preferably 75% or more, and particularly preferably 80% or more, based on the number of particles. By making the content ratio of spherical particles with a sphericity of 0.70 or more and 1.00 or less in the negative thermal expansion material within the above range, the generation of fine particle components caused by debris or the like can be suppressed during the mixing process with the positive thermal expansion material, thereby forming a positive thermal expansion material with excellent dispersibility and filling performance.
[0058] In the present invention, the content ratio of spherical particles with a sphericity of 0.70 or more and 1.00 or less is expressed by observing the sample under an electron microscope at a magnification of 100 to 1000, and randomly extracting 50 particles for image analysis processing, and then calculating the content ratio (percentage) based on the number of particles with a sphericity of 0.70 or more and 1.00 or less in the extracted particles according to the above formula (1).
[0059] Examples of image analysis devices used in the image analysis process include Luzex (manufactured by Nireco) and PITA-04 (manufactured by Seishin Corporation). The closer the value of sphericity is to 1, the closer the shape is to a true sphere.
[0060] The thermal expansion coefficient of the negative thermal expansion material of the present invention is not particularly limited, as long as the thermal expansion coefficient is smaller than that of the copper-vanadium composite oxide powder having the same composition as the general formula (1) in which the Al atoms are not solid-dissolved. The thermal expansion coefficient of the negative thermal expansion material of the present invention is preferably in the range of -10×10 ﹣6 / K or less, more preferably -12×10 ﹣6 / K or less, more preferably -15×10 ﹣6 / K or less; the lower limit is not particularly limited, usually -40×10 ﹣6 / K or more, preferably -37×10 ﹣6 / K or more. In the negative thermal expansion material of the present invention, the thermal expansion coefficient of the negative thermal expansion material of the present invention is preferably -35×10 ﹣6 ~﹣13×10 ﹣6 / K.
[0061] It should be noted that in the present invention, the thermal expansion coefficient is obtained according to the following steps. First, 1.0 g of the negative thermal expansion material sample is mixed with 0.05 g of the binder resin and filled into the mixture. The mold is then formed using a manual press at a pressure of 0.5 t to form a molded body. The molded body is fired in an electric furnace at a temperature of 700°C in an atmospheric environment for 4 hours to obtain a ceramic molded body. Using a thermomechanical measuring device, the obtained ceramic molded body is repeatedly measured twice in a nitrogen environment at a load of 10 g and a temperature range of 50 to 425°C, and the second measurement value in the range of 50 to 400°C in the repeated measurement is used as the thermal expansion coefficient. As a thermomechanical measuring device, for example, TMA4000SE manufactured by NETZSCH JAPAN can be used.
[0062] In the negative thermal expansion material of the present invention, the copper-vanadium composite oxide represented by the general formula (1) basically contains the Ziesite phase (β phase) and the Blossite phase (α phase), and a mixed phase of the two phases also exists. Although the negative thermal expansion material of the present invention may be the Ziesite phase (β phase), the Blossite phase (α phase), or a mixed phase of the Ziesite phase (β phase) and the Blossite phase (α phase), from the perspective of being a material with excellent negative thermal expansion properties after X-ray diffraction analysis of the obtained copper-vanadium composite oxide, it is preferably a composite oxide containing a larger amount of the Ziesite phase (β phase) mixed phase in which the main peak at 2θ=25° due to the Ziesite phase (β phase) is higher than the main peak at 2θ=27° due to the Blossite phase (α phase).
[0063] It should be noted that, in the present invention, the copper-vanadium composite oxide represented by the general formula (1) is a single phase, which means that the Ziesite phase (β phase) of the copper-vanadium composite oxide represented by the general formula (1) exists alone, the Blossite phase (α phase) exists alone, or a mixed phase of the Ziesite phase (β phase) and the Blossite phase (α phase) exists, which means that in X-ray diffraction, no diffraction peak other than the copper-vanadium composite oxide represented by the general formula (1) can be detected.
[0064] In the present invention, the vicinity of 2θ=25° means 2θ=23.5 to 26.5°, and the vicinity of 2θ=27° means 2θ=26.8 to 27.8°.
[0065] In the negative thermal expansion material of the present invention, after X-ray diffraction analysis of the negative thermal expansion material using CuKα rays as the radiation source, it can be seen that the diffraction peak near 2θ=25° originates from the Ziesite phase (β phase), and the diffraction peak near 2θ=27° originates from the Blossite phase (α phase).
[0066] The method for producing the negative thermal expansion material of the present invention is not particularly limited, but industrial production is facilitated by performing the following first step and second step.
[0067] The method for producing a negative thermal expansion material of the present invention is characterized by comprising a first step of mixing an Al source, a Cu source, a V source and an M source added as required to prepare a raw material mixture; and a second step of firing the raw material mixture to obtain a negative thermal expansion material.
[0068] The first step is a step of mixing an Al source, a Cu source, a V source, and an M source added as necessary to prepare a raw material mixture.
[0069] Examples of the Al source in the first step include aluminum oxides, aluminum hydroxides, aluminum nitrate, aluminum sulfate, aluminum dihydrogen phosphate, aluminum chloride, and aluminum lactate.
[0070] Examples of the Cu source in the first step include copper salts of organic carboxylic acids such as copper gluconate, copper citrate, copper acetate, and copper lactate, copper salts of inorganic acids, copper oxides, and copper hydroxides.
[0071] As the V source in the first step, for example, vanadic acid and its sodium salt, potassium salt, ammonium salt, carboxylate, vanadium oxides such as vanadium pentoxide, etc. can be cited. As the vanadium salt of carboxylic acid, monocarboxylates such as formic acid, acetic acid, glycolic acid, lactic acid, gluconic acid, dicarboxylic acids such as oxalic acid, maleic acid, malonic acid, malic acid, tartaric acid, succinic acid, carboxylates of citric acid having 3 carboxyl groups can be cited.
[0072] Examples of the M source to be mixed as necessary in the first step include carboxylates, halides, oxides, hydroxides, etc. of the M source. Examples of the carboxylates of the M source include gluconates, citrates, lactates, etc.
[0073] In the preparation of the raw material mixture of the first step, it is preferred to appropriately adjust the mixing amounts of the Cu source, the V source, and the M source added as needed so that the atomic molar ratios of Cu, V, and M in the raw material mixture become the composition of the copper-vanadium composite oxide represented by the above general formula (1). In addition, in the preparation of the raw material mixture of the first step, the mixing amount of the Al source is preferably adjusted to 100 to 30,000 mass ppm, more preferably 500 to 28,000 mass ppm, and particularly preferably 1,000 to 26,000 mass ppm relative to the obtained negative thermal expansion material.
[0074] In the first step, the Al source, Cu source, V source and, if necessary, M source may be mixed under wet or dry conditions. However, mixing under wet conditions is preferred because a uniform raw material mixture can be easily obtained.
[0075] The solvent used in the wet mixing treatment varies depending on the types of the Al source, the Cu source, the V source, and the M source added as needed, and examples thereof include water, methanol, and ethanol.
[0076] When insoluble or poorly soluble raw materials are used for the Al source, Cu source, V source and the M source added as needed, from the perspective of improving reactivity, the average particle size of the Al source, Cu source, V source and the M source added as needed is preferably an average particle size (D50) of less than 50 μm as determined by laser diffraction method, and particularly preferably 0.1 to 40 μm.
[0077] As Al source, Cu source, V source and M source added as needed, the device for wet mixing treatment when insoluble or insoluble raw materials are used is not particularly limited, as long as a slurry in which each raw material is uniformly dispersed can be obtained. In addition, in the preparation of the slurry, the slurry can be wet-pulverized with a medium mill as needed. As a medium mill, a bead mill, a ball mill, a paint oscillator, a stirring mill, a sand mill and other medium mills can be cited. In addition, when the amount at the laboratory level is small, a mortar or the like can also be used for wet mixing treatment.
[0078] In addition, from the perspective of more efficiently performing wet mixing treatment, a dispersant may be mixed in the slurry. As the dispersant mixed in the slurry, various surfactants, polycarboxylic acid ammonium salts, etc. may be cited. From the perspective of improving the dispersion effect, the dispersant concentration in the slurry is preferably 0.01 to 10% by mass, particularly preferably 0.1 to 5% by mass.
[0079] By completely drying and removing the solvent after the wet mixing treatment, a raw material mixture can be obtained.
[0080] In addition, in the first step, the raw material mixture can also be obtained by removing the aqueous solvent after dissolving the Al source, Cu source, V source and the M source added as needed in an aqueous solvent. In this case, as the Al source, Cu source, V source and the M source added as needed, it is sufficient to use a raw material soluble in an aqueous solvent. As the Al source soluble in an aqueous solvent, for example, aluminum nitrate, aluminum sulfate, aluminum dihydrogen phosphate, aluminum chloride, aluminum lactate, etc. can be cited. As the Cu source, for example, copper salts of organic carboxylic acids, copper salts of inorganic acids, etc. can be cited. In addition, as the V source soluble in an aqueous solvent, vanadic acid and its sodium salt, potassium salt, ammonium salt, carboxylate, etc. can be cited.
[0081] In the case where a vanadium salt of a carboxylic acid is used as the V source in the first step, vanadium pentoxide, a reducing agent and a carboxylic acid can be added to an aqueous solvent, followed by heat treatment at a temperature of 60 to 100° C. to generate a vanadium salt of a carboxylic acid. The reaction solution can be directly used and mixed with a Cu source, an Al source and an M source added as needed to obtain a raw material mixed solution containing the Cu source, the Al source, the V source and the M source added as needed, and then the aqueous solvent can be removed from the raw material mixed solution to prepare a raw material mixture.
[0082] As the reducing agent, reducing sugar is preferred. Examples of reducing sugars include glucose, fructose, lactose, maltose, sucrose, etc. Among them, lactose and sucrose are particularly preferred from the perspective of excellent reaction performance. The amount of reducing sugar added is preferably 0.7 to 3.0 in terms of the molar ratio (C / V) of C in the reducing sugar to V in vanadium pentoxide, and more preferably 0.8 to 2.0 in terms of being able to more efficiently carry out the reduction reaction. The amount of carboxylic acid added is preferably 0.1 to 4.0 in terms of the molar ratio relative to vanadium pentoxide, and more preferably 0.2 to 3.0 in terms of more efficiently obtaining a transparent vanadium solution.
[0083] It should be noted that in the first step, the composition of the copper-vanadium composite oxide represented by the above general formula (1) obtained by drying and removing the solvent after the wet mixing treatment is roughly consistent with the atomic molar ratio of Al, Cu, V and M in the Al source, Cu source, V source and M source added as needed when each raw material is fed.
[0084] The second step is a step of firing the raw material mixture prepared in the first step to obtain the negative thermal expansion material of the present invention.
[0085] The firing temperature in the second step is preferably 580 to 780°C, more preferably 600 to 750°C. On the other hand, when the firing temperature in the second step is lower than the above range, the formation of the copper-vanadium composite oxide represented by the general formula (1) is often insufficient; and when it exceeds the above range, it is often difficult to recover the product due to welding with a crucible, etc. The firing time in the second step is not particularly limited, and the firing is performed for a sufficient time until the negative thermal expansion material of the present invention is formed.
[0086] The firing time in the second step is not particularly limited, and the firing is performed for a sufficient time until the negative thermal expansion material of the present invention is generated. The generation of the negative thermal expansion material of the present invention can be confirmed by, for example, whether a single-phase copper-vanadium composite oxide represented by the general formula (1) is obtained in X-ray diffraction analysis. In the second step, in most cases, within a firing time of more than 1 hour, preferably 2 to 20 hours, almost all of the raw materials in the raw material mixture are formed into a negative thermal expansion material containing the copper-vanadium composite oxide represented by the general formula (1) in which Al atoms are solid-dissolved. It should be noted that the copper-vanadium composite oxide represented by the general formula (1) in the present invention is a single phase, which means that the Ziesite phase (β phase) of the copper-vanadium composite oxide represented by the general formula (1) exists alone, the Blossite phase (α phase) exists alone, or there is a mixed phase of the Ziesite phase (β phase) and the Blossite phase (α phase), which means that no diffraction peak other than the copper-vanadium composite oxide represented by the general formula (1) can be detected in the X-ray diffraction analysis.
[0087] The firing environment in the second step is not particularly limited, and may be any of an inert gas environment, a vacuum environment, an oxidizing gas environment, and air.
[0088] In the second step, the calcination may be performed once or a plurality of times as required. For example, in order to make the powder properties uniform, the mixture calcined once may be pulverized and the pulverized product may be further calcined.
[0089] After firing, the mixture is cooled appropriately and crushed, broken, classified, etc. as required to obtain the negative thermal expansion material of the present invention.
[0090] As a method for manufacturing a negative thermal expansion material having a spherical particle shape, there can be cited a method of drying the slurry after the wet mixing treatment by a spray drying method using a spray dryer, drying all the materials after the wet mixing treatment in the above-mentioned first step, and then performing the above-mentioned second step to manufacture a negative thermal expansion material in which the content ratio of spherical particles with a sphericity of 0.70 or more and 1.00 or less is 75% or more, preferably 80% or more on a number basis.
[0091] In the spray drying method, the droplet size after atomization is preferably, but not particularly limited to, 1 to 40 μm, particularly preferably 5 to 30 μm. The amount of slurry supplied to the spray dryer is preferably determined in consideration of this point.
[0092] It should be noted that the temperature of hot air used for drying in the spray dryer is preferably 100 to 270° C., preferably 150 to 230° C., because this can prevent the powder from absorbing moisture and makes it easy to recover the powder.
[0093] The negative thermal expansion material obtained by the method for producing a negative thermal expansion material of the present invention preferably has an average particle size of 0.1 to 100 μm, particularly preferably 0.3 to 80 μm, and a BET specific surface area of 0.05 to 50 m 2 / g, particularly preferably 0.10 to 10 m 2 The average particle size and / or BET specific surface area of the negative thermal expansion material within the above range is preferred because it facilitates handling of the negative thermal expansion material when used as a filler for resin, glass, etc.
[0094] In addition, the negative thermal expansion material of the present invention can also be surface treated on the particle surface as required for the purpose of improving the resin dispersibility and / or the moisture resistance of the negative thermal expansion material. In addition, the preparation method of the negative thermal expansion material of the present invention can also be surface treated on the negative thermal expansion material obtained by firing as required for the purpose of improving the resin dispersibility and / or the moisture resistance of the negative thermal expansion material.
[0095] As surface treatment, for example, a method of coating the particle surface with a silane coupling agent, a titanate coupling agent, a fatty acid or a derivative thereof, an inorganic compound containing one or more elements selected from Zn, Si, Al, Ba, Ca, Mg, Ti, V, Sn, Co, Fe and Zr, etc. (for example, with reference to WO2020 / 095837, WO2020 / 261976, WO2019 / 087722, and Japanese Patent Application Publication No. 2020-147486) can be cited. In addition, these treatments can also be appropriately combined for surface treatment.
[0096] The thermal expansion coefficient of the negative thermal expansion material obtained by the method for producing the negative thermal expansion material of the present invention is -10×10 ﹣6 / K or less, preferably -12×10 ﹣6 / K or less, more preferably -15×10 ﹣6 / K or less, the lower limit is usually -40×10 ﹣6 / K or more, preferably -37×10 ﹣6 / K or more. The thermal expansion coefficient of the negative thermal expansion material obtained by the method for producing a negative thermal expansion material of the present invention is preferably -35×10 ﹣6 ~﹣13×10 ﹣6 / K.
[0097] The negative thermal expansion material of the present invention is used in the form of powder or paste. When the negative thermal expansion material of the present invention is used in a paste state, the negative thermal expansion material of the present invention is mixed and dispersed in a solvent and / or a low-viscosity liquid resin and used in a paste state. In addition, the negative thermal expansion material of the present invention can also be dispersed in a solvent and / or a low-viscosity liquid resin, and then it can contain an adhesive, a soldering flux, a dispersant, etc. as needed, and used in a paste state.
[0098] The negative thermal expansion material of the present invention can be used as a composite material in combination with various organic compounds or inorganic compounds as positive thermal expansion materials. The composite material of the present invention comprises the negative thermal expansion material of the present invention and a positive thermal expansion material.
[0099] As the organic compound used as the positive thermal expansion material, rubber, polyolefin, polycycloolefin, polystyrene, ABS, polyacrylate, polyphenylene sulfide, phenolic resin, polyamide resin, polyimide resin, epoxy resin, silicone resin, polycarbonate resin, polyethylene resin, polypropylene resin, polyethylene terephthalate resin (PET resin) and polyvinyl chloride resin etc. can be cited but are not particularly limited to. In addition, as the inorganic compound used as the positive thermal expansion material, silicon dioxide, silicate, graphite, sapphire, various glass materials, concrete materials, various ceramic materials etc. can be cited.
[0100] Since the composite material of the present invention includes the negative thermal expansion material of the present invention having excellent negative thermal expansion performance, it can achieve negative thermal expansion coefficient, zero thermal expansion coefficient or low thermal expansion coefficient according to the mixing ratio of the negative thermal expansion material with other compounds.
[0101] Example
[0102] The present invention is described below by way of examples, but the present invention is not limited thereto.
[0103] (X-ray diffraction device)
[0104] In the examples, the measurement was performed using an X-ray diffraction apparatus (Ultima IV manufactured by Rigaku Corporation) under the following measurement conditions.
[0105] Radiation source: Cu-Kα
[0106] Tube voltage: 40kV
[0107] Tube current: 40mA
[0108] Scanning speed: 4° / sec
[0109] (Example 1)
[0110] (First process)
[0111] 3.00 g of ammonium vanadate (NH4VO3), 6 ml of ammonia water, and 80 ml of pure water were added to a beaker, and heated at 60°C under stirring to obtain solution A. Then, 11.64 g of copper gluconate (manufactured by Fuso Chemical Industry) was added to 50 ml of pure water and stirred to obtain solution B. Then, 0.24 g of aluminum nitrate nonahydrate was added to 10 ml of pure water and stirred to obtain solution C. Then, solution B and solution C were added to solution A in sequence to obtain a raw material mixed solution in which each raw material was dissolved.
[0112] The obtained raw material mixed liquid was heated at a temperature that kept it in a boiling state while being stirred to remove water, thereby obtaining a paste-like raw material mixture.
[0113] (Second process)
[0114] The obtained paste-like raw material mixture was fired in a crucible at 700° C. for 4 hours in an atmospheric environment to obtain a fired product.
[0115] X-ray diffraction analysis of the sintered product revealed that a single-phase Ziesite phase Cu with a main diffraction peak near 2θ = 25° was detected. 2.00 V 2.00 O 7.00 The X-ray diffraction pattern of the fired product is shown in Figure 1 . In addition, the solution obtained by acid decomposition of the obtained fired product was subjected to ICP emission analysis to determine the content of Al atoms in the fired product. The results showed that the content of Al atoms was 3980 mass ppm. From these results, it can be seen that the fired product is a single-phase Ziesite copper-vanadium composite oxide with 3980 mass ppm of Al atoms dissolved in a solid solution.
[0116] The fired product was then pulverized in a mortar and used as a negative thermal expansion material sample.
[0117] It should be noted that when 50 particles randomly selected from the negative thermal expansion material sample were observed using an electron microscope (magnification 400), the particle shape was found to be fragmentary.
[0118] (Example 2)
[0119] (First process)
[0120] 3.00 g of ammonium vanadate (NH4VO3), 6 ml of ammonia water, and 80 ml of pure water were added to a beaker, and heated at 60°C under stirring to obtain solution A. Then, 11.06 g of copper gluconate (manufactured by Fuso Chemical Industry) was added to 50 ml of pure water and stirred to obtain solution B. Then, 0.48 g of aluminum nitrate nonahydrate was added to 10 ml of pure water and stirred to obtain solution C. Then, solution B and solution C were added to solution A in sequence to obtain a raw material mixed solution in which each raw material was dissolved.
[0121] The raw material mixed liquid was heated at a boiling temperature while being stirred to remove water, thereby obtaining a paste-like reaction mixture.
[0122] (Second process)
[0123] The pasty reaction mixture was fired in a crucible at 700° C. for 4 hours in an atmospheric environment to obtain a fired product.
[0124] X-ray diffraction analysis of the sintered product revealed that a single-phase Ziesite phase Cu with a main diffraction peak near 2θ = 25° was detected. 2.00 V 2.00 O 7.00 The X-ray diffraction pattern of the fired product is shown in Figure 2 . In addition, the solution obtained by acid decomposition of the obtained fired product was subjected to ICP emission analysis to determine the content of Al atoms in the fired product. The results showed that the content of Al atoms was 8000 mass ppm. From these results, it can be seen that the fired product is a single-phase Ziesite copper-vanadium composite oxide with 8000 mass ppm of Al atoms dissolved in a solid solution.
[0125] The fired product was then pulverized in a mortar and used as a negative thermal expansion material sample.
[0126] It should be noted that when 50 particles randomly selected from the negative thermal expansion material sample were observed using an electron microscope (magnification 400), the particle shape was found to be fragmentary.
[0127] (Example 3)
[0128] (First process)
[0129] 3.00 g of ammonium vanadate (NH4VO3), 6 ml of ammonia water, and 80 ml of pure water were added to a beaker, and heated at 60°C under stirring to obtain solution A. Then, 10.19 g of copper gluconate (manufactured by Fuso Chemical Industry) was added to 50 ml of pure water and stirred to obtain solution B. Then, 1.20 g of aluminum nitrate nonahydrate was added to 20 ml of pure water and stirred to obtain solution C. Then, solution B and solution C were added to solution A in sequence to obtain a raw material mixed solution in which each raw material was dissolved.
[0130] The raw material mixture was heated at a temperature that kept the mixture in a boiling state while being stirred to remove water, thereby obtaining a paste-like raw material mixture.
[0131] (Second process)
[0132] The paste-like raw material mixture was fired in a crucible at 700° C. for 4 hours in an atmospheric environment to obtain a fired product.
[0133] X-ray diffraction analysis of the sintered product revealed that a single-phase Ziesite phase Cu with a main diffraction peak near 2θ = 25° was detected. 2.00 V 2.00 O 7.00 The X-ray diffraction pattern of the fired product is shown in Figure 3In addition, the solution obtained by acid decomposition of the obtained fired product was subjected to ICP emission analysis to determine the content of Al atoms in the fired product. The results showed that the content of Al atoms was 20330 mass ppm. From these results, it can be seen that the fired product is a single-phase Ziesite copper-vanadium composite oxide with 20330 mass ppm of Al atoms dissolved in a solid solution.
[0134] The fired product was then pulverized in a mortar and used as a negative thermal expansion material sample.
[0135] It should be noted that when 50 particles randomly selected from the negative thermal expansion material sample were observed using an electron microscope (magnification 400), the particle shape was found to be fragmentary.
[0136] (Comparative Example 1)
[0137] 1.71 g of vanadium pentoxide (V2O5, average particle size 1.0 μm) and 1.50 g of copper oxide (CuO, average particle size 1.5 μm) were ground and mixed in a mortar with 30 ml of ethanol as a dispersion medium for 20 minutes and then dried to obtain a raw material mixture. The powder was fired at 650°C for 4 hours in an atmospheric environment to obtain a fired product.
[0138] The obtained fired product was subjected to X-ray diffraction analysis and the results showed that a single-phase Cu Blossite phase with a main diffraction peak near 2θ = 27° was detected. 2.00 V 2.00 O 7.00 The X-ray diffraction pattern of the fired product is shown in Figure 4 .
[0139] That is, in Comparative Example 1, no Al source was used, and the obtained copper-vanadium composite oxide of Cu2V2O7 was not an oxide in which Al atoms were solid-dissolved.
[0140] The fired product was then pulverized in a mortar and used as a negative thermal expansion material sample.
[0141] It should be noted that when 50 particles randomly selected from the negative thermal expansion material sample were observed using an electron microscope (magnification 400), the particle shape was found to be fragmentary.
[0142] (Physical Property Evaluation)
[0143] The average particle size, BET specific surface area and thermal expansion coefficient of the negative thermal expansion material samples obtained in the examples and comparative examples were measured. It should be noted that the average particle size and thermal expansion coefficient were measured as follows. The results are shown in Table 1.
[0144] (Average particle size)
[0145] The negative thermal expansion material sample was observed with a scanning electron microscope at a magnification of 1000 times, and the longest particle diameters of 50 particles randomly selected from the observation field were measured. Their arithmetic mean was calculated as the average particle diameter of the negative thermal expansion material sample.
[0146] (Measurement of thermal expansion coefficient)
[0147] <Preparation of Molded Body>
[0148] 0.05 g of propylene carbonate was added to 1.00 g of the sample, and the mixture was ground and mixed in a mortar for 3 minutes. Then 0.15 g of the mixture was weighed and filled into a mortar. The powder was then pressed into a mold using a manual press at a pressure of 0.5 t to form a powder compact. The obtained powder compact was heated to 700°C in an electric furnace over 3 hours and kept at this temperature for 4 hours to form a ceramic compact.
[0149] <Measurement of thermal expansion coefficient>
[0150] The thermal expansion coefficient of the obtained ceramic molded body was measured using a thermomechanical measuring device (TMA4000SE manufactured by NETZSCH JAPAN). The measurement conditions were set to a nitrogen environment, a load of 10 g, and a temperature range of 50°C to 425°C, and the measurement was repeated twice. The thermal expansion coefficient in the range of 50 to 400°C measured for the second time was set as the thermal expansion coefficient of the negative thermal expansion material sample.
[0151] [Table 1]
[0152]
[0153] It should be noted that the linear expansion coefficient of the negative thermal expansion material sample of Comparative Example 1 within the range of 50 to 300°C is -4.4×10 ﹣6 / K.
[0154] (Example 4)
[0155] Weigh 16.2 parts by mass of vanadium pentoxide (V2O5, average particle size 1.0 μm), 13.5 parts by mass of copper oxide (CuO, average particle size 1.5 μm), and 0.5 parts by mass of aluminum hydroxide (Al(OH)3, average particle size 1.2 μm), and stir for 30 minutes using 69.7 parts by mass of pure water as a dispersion medium to prepare a 30.2% by mass slurry.
[0156] Then, 0.1 parts by mass of polycarboxylic acid ammonium salt was added to the slurry as a dispersant, and zirconium oxide beads with a diameter of 0.5 mm were added while the slurry was stirred. Then, the slurry was supplied to a medium stirring bead mill and wet-milled. The average particle size of the solid component after wet milling was obtained by laser diffraction scattering method, and the result was 0.54 μm.
[0157] Next, the slurry after the wet pulverization treatment was supplied to a spray dryer set at 220° C. at a supply rate of 3.3 L / h and spray-dried to obtain a raw material mixture.
[0158] Then, the raw material mixture was fired at 700°C for 4 hours in an atmospheric environment to obtain a fired product. X-ray diffraction analysis of the fired product revealed that a single-phase Ziesite phase Cu with a main diffraction peak near 2θ=25° was detected. 2.00 V 2.00 O 7.00 . In addition, the solution obtained by acid decomposition of the obtained fired product was subjected to ICP emission analysis to determine the content of Al atoms in the fired product. The results showed that the content of Al atoms was 5600 mass ppm. From these results, it can be seen that the fired product is a single-phase Ziesite copper-vanadium composite oxide with 5600 mass ppm of Al atoms dissolved in a solid solution.
[0159] The fired product was then pulverized in a mortar and then pulverized with a jet mill to obtain a pulverized product, which was used as a negative thermal expansion material sample.
[0160] It should be noted that observation of 50 particles randomly extracted from the negative thermal expansion material sample using an electron microscope (magnification 400) showed that the particle shape was spherical.
[0161] (Example 5)
[0162] A pulverized product was obtained in the same manner as in Example 4 except that the firing temperature of the raw material mixture was 650°C.
[0163] The X-ray diffraction analysis of the obtained pulverized product confirmed that it was a copper-vanadium composite oxide (Cu 2.00 V 2.00 O 7.00 ) single phase, with a main diffraction peak due to the Ziesite phase near 2θ = 25°, and a diffraction peak of the Blossite phase was also observed near 2θ = 27°. It formed a negative thermal expansion material sample with 5600 mass ppm of Al atoms dissolved in a solid solution.
[0164] It should be noted that observation of 50 particles randomly extracted from the negative thermal expansion material sample using an electron microscope (magnification 400) showed that the particle shape was spherical.
[0165] (Example 6)
[0166] Weigh 16.2 parts by mass of vanadium pentoxide (V2O5, average particle size 1.0 μm), 13.4 parts by mass of copper oxide (CuO, average particle size 1.5 μm), 0.5 parts by mass of aluminum hydroxide (Al(OH)3, average particle size 1.2 μm), and 0.2 parts by mass of calcium carbonate (CaCO3, average particle size 2.4 μm), use 69.7 parts by mass of pure water as a dispersion medium, and stir for 30 minutes to make a 30.3% by mass slurry.
[0167] Then, 0.1 parts by mass of polycarboxylic acid ammonium salt was added to the slurry as a dispersant, and zirconium oxide beads with a diameter of 0.5 mm were added while the slurry was stirred. Then, the slurry was supplied to a medium stirring bead mill and wet-milled. The average particle size of the solid component after wet milling was obtained by laser diffraction scattering method, and the result was 0.52 μm.
[0168] Next, the slurry after the wet pulverization treatment was supplied to a spray dryer set at 220° C. at a supply rate of 3.3 L / h and spray-dried to obtain a raw material mixture.
[0169] Then, the raw material mixture was fired at 700°C for 4 hours in an atmospheric environment to obtain a fired product. X-ray diffraction analysis of the fired product revealed that a single-phase Ziesite phase Cu with a main diffraction peak near 2θ=25° was detected. 2.00 V 2.00 O 7.00 The obtained fired product was subjected to acid decomposition and the obtained solution was subjected to ICP emission analysis to determine the content of Al atoms in the fired product. The results showed that the content of Al atoms was 5600 mass ppm. These results show that the fired product is a single-phase Ziesite phase copper-vanadium composite oxide (Cu 1.98 Ca 0.02 V 2.00 O 7.00 ).
[0170] The fired product was then pulverized in a mortar and then pulverized using a jet mill to obtain a pulverized product, which was used as a negative thermal expansion material sample.
[0171] It should be noted that observation of 50 particles randomly extracted from the negative thermal expansion material sample using an electron microscope (magnification 400) showed that the particle shape was spherical.
[0172] (Physical Property Evaluation)
[0173] The average particle size, BET specific surface area and thermal expansion coefficient of the negative thermal expansion material samples obtained in Examples 4, 5 and 6 were measured in the same manner as in Examples 1 to 3. The content ratio of spherical particles was obtained by the following method. In addition, the SEM photograph of the negative thermal expansion material sample obtained in Example 4 is shown in Figure 5 .
[0174] (Measurement of the content ratio of spherical particles)
[0175] The sphericity of 50 particles randomly extracted at a magnification of 400 times was calculated using an image analyzer Luzex (manufactured by Nireco) according to the following formula, and the content ratio of spherical particles having a sphericity of 0.70 or more and 1.00 or less on a number basis was evaluated.
[0176] Sphericity = area equivalent circle diameter / circumscribed circle diameter (1)
[0177] Area equivalent circle diameter: The diameter of a circle whose circumference is equal to the circumference of a particle.
[0178] Circumscribed circle diameter: the longest diameter of a particle.
[0179] [Table 2]
[0180]
[0181] It should be noted that, although the negative thermal expansion material sample of Example 5 has the same Al atomic content as the negative thermal expansion material of Example 4, the negative thermal expansion performance of the sample of Example 5 with the firing temperature set to 650°C is better than that of the negative thermal expansion material sample of Example 4 with the firing temperature set to 700°C. The inventor believes that this is because, in the preparation of the ceramic molded body for measuring the thermal expansion coefficient, when fired at a temperature of 700°C, the transformation of the Blossite phase to the Ziesite phase in the copper-vanadium composite oxide in the negative thermal expansion material sample of Example 5 is promoted, and when fired at a temperature of 700°C, each particle will further grow, thereby further reducing the gap between the particles of the ceramic molded body itself, so compared with the ceramic molded body prepared using the negative thermal expansion material of Example 4, the ceramic molded body prepared using the negative thermal expansion material of Example 5 can obtain a denser product.
Claims
1. A negative thermal expansion material, characterized in that: A copper-vanadium composite oxide powder having Al atoms dissolved therein and represented by the following general formula (1) is included. With x M y V z A t (1) In the formula, M represents a metal element with an atomic number of 11 or above other than Cu, V and Al, x represents 1.60≤x≤2.40, y represents 0.00≤y≤0.40, z represents 1.70≤z≤2.30, and t represents 6.00≤t≤9.00, wherein 1.00≤x+y≤3.00, and, in the case of containing the M element, the atomic-converted molar number of Al atoms is greater than the atomic-converted molar number of M atoms.
2. The negative thermal expansion material according to claim 1, characterized in that In the general formula (1), M is one or more metal elements selected from Zn, Ga, Fe, Mg, Co, Mn, Ba and Ca.
3. The negative thermal expansion material according to claim 1, characterized in that In the general formula (1), M is Ca.
4. The negative thermal expansion material according to claim 1 or 2, characterized in that: The content of Al atoms in the negative thermal expansion material is 100 to 30000 mass ppm.
5. The negative thermal expansion material according to claim 1 or 2, characterized in that: Thermal expansion coefficient is -10×10 ﹣6 / K or less.
6. The negative thermal expansion material according to claim 1 or 2, characterized in that: The average particle size is 0.1 to 100 μm.
7. The negative thermal expansion material according to claim 1 or 2, characterized in that: BET specific surface area is 0.05~50m 2 / g.
8. The negative thermal expansion material according to claim 1 or 2, characterized in that: The content ratio of spherical particles having a sphericity of 0.7 or more and 1.0 or less is 75% or more on a number basis.
9. A method for manufacturing a negative thermal expansion material, characterized in that: The negative thermal expansion material comprises the copper-vanadium composite oxide powder according to claim 1, having A first step of mixing an Al source, a Cu source, a V source, and an M source as needed to prepare a raw material mixture; and The second step is to sinter the raw material mixture to obtain a negative thermal expansion material.
10. The method for manufacturing a negative thermal expansion material according to claim 9, wherein: The first step includes a step of preparing a raw material mixed solution in which an Al source, a Cu source, a V source, and an M source added as needed are dissolved in an aqueous solvent.
11. The method for manufacturing a negative thermal expansion material according to claim 9, wherein: In the first step, a slurry containing an Al source, a Cu source, a V source, and an M source added as needed is prepared, and the slurry is dried by a spray drying method.
12. A composite material, characterized in that: The invention comprises the negative thermal expansion material and the positive thermal expansion material as claimed in claim 1.
13. The composite material according to claim 12, characterized in that The positive thermal expansion material is at least one selected from metal, alloy, glass, ceramic, rubber and resin.
Citation Information
Patent Citations
Sealing material
JP2005035840A
Negative-expansion ceramic
JP2015010006A
Negative thermal expansion material and composite material containing the same
JP2018002577A
Negative thermal expansion material and composite
JP2019210198A
Modified zirconium phosphate tungstate, negative thermal expansion filler, and polymeric composition
JP2020147486A
Cited By
Negative thermal expansion material beta-Cu 2-x Zn x V2O7 and methods of making and using the same
CN122977440A